Sustainability and Empowerment in Context of Inclusion of Disabled Persons - Moceviciene, Aldona; Strods, Gunars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Creation without disassembling, using wisely, responsible  planing and estimation longer-term consequences giving priority to the person, respecting his/her individuality, diversity - this is a new approach and sustainable society features. Quality of life include all aspects of the way we live our lives. They allow us to fulfil our needs and aspirations. On the basis of results of the research EU policy materials and Lithuania and Latvia ways of realization these laws in the regional policy, that all global methods and wellbeing development actions have a direct impact for  people with intellectual  disabilitiess and influentto expanding possibilities self-expression, activating self-action, stimulating self-conception. Creatiwity –the way and possibility in empowering these people socialization and self – realizing. The researches in this field would answer to the questons: possible to optimize the quality of life  for people with intellectual deseases in their abilities limited space.